Modeling and ID Compensation of TRIBs Beam Optics at the MAX IV 1.5 GeV Storage Ring - Petersson,Alfred (2026)
Transverse Resonant Island Buckets (TRIBs) is a promising method for pseudo-single bunch delivery in the MAX IV 1.5 GeV storage ring. In this thesis, a theoretical model of the non-linear optics based on resonant Hamiltonian mechanics is applied to the TRIBs optics. Measurement techniques for characterizing the TRIBs orbit are developed and tested and compared with theoretical predictions and numerical tracking. As the TRIBs optics in the 1.5 GeV ring has previously been found to be sensitive to the impact of insertion devices (IDs), the effects of the IDs are analyzed in the Hamiltonian framework. A novel sextupole correction scheme for TRIBs optics ID compensation is presented, achieved by optimizing the sextupole magnet strengths such that the parameters of the resonant Hamiltonian stay constant. A potential feedforward implementation of the compensation scheme is tested, which is successfully used to correct for an ID.
Keywords: TRIBs; Non-linear optics; Hamiltonian mechanics; Resonance; Insertion device; MAX IV; Accelerator physics